Listening to Mr. Bob Kampung Inggris: A Quasi Experimental Design - Wahyuni, Tri; Wijaya, M. Sayid; Aryanika, Septa (Journal of Linguistics and Social Sciences, 2026)
Listening is an essential skill in learning English as it enables students to understand spoken language and communicate effectively. However, many students still experience difficulties in listening due to limited learning media, lack of practice, and less engaging teaching methods. Therefore, technology-based media such as YouTube podcasts are expected to support the improvement of students’ listening skills. This study aimed to examine the effect of using the Mr. Bob Kampung Inggris Podcast YouTube Channel on the listening skills of tenth-grade students at MAN 2 Bandar Lampung. The research employed a quantitative method with a quasi-experimental design, specifically a non-equivalent control group design. The sample consisted of two classes: an experimental class taught using the Mr. Bob Kampung Inggris podcast on YouTube and a control class taught using conventional listening materials. Both groups were given a pre-test and a post-test in the form of multiple-choice listening tests. The data were analyzed using an independent samples t-test. The result showed that the significance value (Sig. 2-tailed) was 0.740, which was higher than 0.05, indicating that there was no statistically significant difference between the post-test scores of the experimental and control groups. Although the experimental class obtained a slightly higher mean score which was 77.27 than the control class which was 76.52, the difference was not statistically significant. Therefore, the use of the Mr. Bob Kampung Inggris Podcast YouTube Channel has no significant influence on students’ listening skills.